Risk assessment of orthodontic anomalies in children in suburban areas - Radumilo Danijela; Vučinić Predrag; Ivić Stojan; Petrović Đorđe (Medicinski fakultet i Klinika za stomatologiju, Niš, 2021)
Introduction: Orthodontic anomalies are very common both in the world and in our country. The etiology of orthodontic anomalies is multifactorial, complex and conditioned by numerous genetic and non-genetic factors: endogenous and exogenous. Prevention of orthodontic anomalies is possible if we have an insight into the most common etiological factors. Goal: To assess the frequency of individual etiological factors and assess the overall risk of orthodontic anomalies in children in suburban environments. Materials and methods: The research was conducted on 115 children, first grade elementary school pupils (28.68% of all 1st grade students), average age of 6.8 years, from 4 settlements around Novi Sad: Kisač, Kać, Veternik, and Futog. The research was conducted in the form of anonymous rounding surveys for parents with a preliminary explanation of the questions asked. The questions included etiological factors for the occurrence of orthodontic anomalies (diseases in pregnancy, childbirth, breastfeeding, supplementation and feeding, type of pacifier, position of the bottle when eating, bad habits, position when sleeping, position of arms when sleeping in relation to the jaw, pillow height, mouth breathing, orthodontic anomalies in parents). Results: Results indicate the following etiological factors as the most common: supplementary feeding and bottle feeding (in 41.74% of cases), breastfeeding from 0 to 6 months (40.87% of respondents) and mouth breathing (in 24.35% of children). In the examination of the total risk for orthodontic anomalies, low-risk was found in 95.65% of cases, medium-risk in 4.35% (in Kisac 9.38%, in Kać 2.94%, in Veternik 4.35%, in Futog 0% of children), while there were no high-risk respondents. Conclusion: Preventive measures should be aimed at educating mothers about the need and benefits of a natural way of breastfeeding and of using a spoon for supplementation and feeding.